The Influence of Academic Supervision and Infrastructure on Teacher Performance Through Motivation in Public Elementary Schools in Sirampog District - Irawan, Oji Bambang; Oktarina, Nina (Universitas Negeri Semarang, 2025)
This study aims to analyze the effect of academic supervision and school infrastructure on teacher performance through motivation as an intervening variable in public elementary schools in Sirampog District. Using a quantitative approach and path analysis method, the study involved 207 elementary school teachers selected through proportionate stratified random sampling. Data were collected using a validated and reliable questionnaire and analyzed using regression analysis, Sobel test, and path analysis. The results showed that academic supervision and infrastructure had a significant and positive effect on motivation and teacher performance. Moreover, motivation partially mediated the influence of both academic supervision and infrastructure on performance. These findings highlight the importance of strengthening academic supervision and improving infrastructure to foster teacher motivation and enhance performance.